La ley contra la violencia a la mujer y la familia, en el art. 13, medidas de amparo numeral 3, establece la prohibición al agresor de acercarse a la agredida en su lugar de trabajo o de estudio, sin precisar circunstancias en que puede haber la aproximación, lugares públicos, en establecimientos educativos, por lo que es necesario reformar esta disposición - Arana Viteri, Hugo José (2014)
This legal research is part of academic problems, and within family law, particularly the Law Against Violence Against Women and Family in the investigation is part of an issue of socio-legal reality develop, which is the same as domestic violence has increased to new levels, with schools as the destruction of the family environment, termination of marriage, injury, and sometimes death of family members especially women. This type of violence is committed in the home or outside of it, but always by a relative or former relative by marriage or blood relative (parent, stepparent, spouse (s) or partner (a), uncles (as), cousins (as), father (as), etc. domestic violence is one that occurs within the family, may be the perpetrator shares or has shared the same residence, this type of violence includes rape, physical abuse, psychological and sexual abuse. To carry out research on the family or domestic violence, it is part of a conceptual theoretical analysis covers what is domestic violence causes: economic, emotional, characterological and otherwise, of the consequences stemming from domestic violence such as the destruction of the family environment, marriage, problems that children and other family members who suffer the consequences of these acts extend; then a focus on the implications of domestic violence in the constitutional and legal level, ie the analysis of the Constitution regarding the rights of individuals, families, domestic violence is made; Analysis of the Law on Violence against Women and the Family, and other related laws, comparative law study about domestic violence. Then he proceeds to conduct a field study involving analysis of the result of the application of techniques such as bibliographic signing, the investigation of criteria that people have in relation to domestic violence, this, based on surveys and interviews, same to be tabulated and analyzed statistically and graphically. Initially objectives of general and specific nature were proposed, as well as the respective hypotheses, objectives plotted the route to be followed by the research carried out. Finally a proposed amendment to the Law on Violence against Women and Families arises. Central motif of this thesis is a detailed study of so-called protection measures, contained in the Law on Violence against Women and the Family and in particular to that extent which prevents the approach of the abused abuser, whose central question is that of the ambiguity of the rule does not state explicitly and places strict approach which is not allowed, according to the analysis there are circumstances in which you can not avoid such a meeting a couple, circumstances are disclosed in the course of work.